2008
DOI: 10.1159/000116882
|View full text |Cite
|
Sign up to set email alerts
|

Testing Three Different Cancer Genetics Registry Recruitment Methods with Hispanic Cancer Patients and Their Family Members Previously Registered in Local Cancer Registries in Texas

Abstract: Objective: To increase accrual among Hispanics to the Cancer Genetics Network national cancer genetics registry. Methods: Drawing from South Texas cancer registries, 444 Hispanic men and women were randomly assigned to one of three experimental conditions: standard direct-mailed procedures (X1), X1 plus culturally tailored materials (X2), and X2 plus interpersonal phone contact (X3). Participants were also surveyed about the effectiveness of the education materials and the phone contact. A refusal survey was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Of these 25 citations, 14 are related to cancer (6 to breast cancer [10-14, 16,17], 2 to ovarian cancer [18-19], 1 to hematological cancer [20], 1 to prostate cancer[13], 1 to cancer genetics [21], 1 to histiocytosis [22], 1 to familial adenomatous polyposis [23], and 1 to colorectal cancer [24]), 3 to diabetes mellitus [25-27], 1 to stroke [28], 1 to asthma [29], 1 to celiac disease [30] and 5 are disease neutral [9, 15, 31-33]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 25 citations, 14 are related to cancer (6 to breast cancer [10-14, 16,17], 2 to ovarian cancer [18-19], 1 to hematological cancer [20], 1 to prostate cancer[13], 1 to cancer genetics [21], 1 to histiocytosis [22], 1 to familial adenomatous polyposis [23], and 1 to colorectal cancer [24]), 3 to diabetes mellitus [25-27], 1 to stroke [28], 1 to asthma [29], 1 to celiac disease [30] and 5 are disease neutral [9, 15, 31-33]. …”
Section: Resultsmentioning
confidence: 99%
“…The CARE colorectal cancer screening trial used 5 tumor registries in the US [24]. The cancer genetics clinical trial used local cancer registries in US [21], the histiocytosis registry was a national registry in Spain [22] and the hematological cancer trial used a state registry in Australia [20]. In the 3 registries related to diabetes, the first used a quality improvement registry in an US medical center [25], the second, an international study, used center specific type 1 diabetes registries (without specifying the center location) [26], and the third used central and local registers in the UK [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary concern in the use of biospecimen donation for genetic studies is a lack of the public’s understanding of genetics and genetic research (Streicher et al 2011) and a reluctance to donate tissue and/or visit a medical facility for biospecimen collection (Dang et al 2014). Previous work has shown that the use of written materials and follow-up phone calls that are in-language and supplemented with verbal explanations by phone increases participation in research among diverse populations (Ramirez et al 2008). As recommended, we used a linguistically, culturally, and educationally tailored recruitment strategy and in-home self-collection protocol for biospecimen donation.…”
Section: Discussionmentioning
confidence: 99%
“…47 They described CBPR projects that attracted rural dwelling adults to cancer screening for the first time 40 ; increased breast and cervical cancer screening among Vietnamese, Hmong, Micronesian, Hispanics, and African-American women 17,23,48–50 ; increased colorectal cancer screening among Chinese Americans, 44 Hispanics, 51,52 and African Americans 53 ; increased Pap test follow-up among American Indian women 54 ; increased hepatitis B immunization among Asian Americans 55 ; increased prostate cancer screening among African Americans 56,57 ; and increased minority participation in clinical trials. 58,59 …”
Section: Resultsmentioning
confidence: 99%